2004
DOI: 10.1093/toxsci/kfh298
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Brominated Flame Retardant, Tetrabromobisphenol-A, on Free Radical Formation in Human Neutrophil Granulocytes: The Involvement of the MAP Kinase Pathway and Protein Kinase C

Abstract: This study investigates the effects of one of the most frequently used brominated flame-retardants (BFR), tetrabromobisphenol-A (TBBPA), on formation of reactive oxygen species (ROS) and calcium levels in human neutrophil granulocytes. TBBPA enhanced ROS production in a concentration-depended manner (1-12 microM), measured as 2,7-dichlorofluorescein diacetate amplified (DCF) fluorescence. The results on ROS production by TBBPA was confirmed by lucigenin-amplified chemiluminescence. The TBBPA induced formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 48 publications
3
56
0
Order By: Relevance
“…# Differences statistically significant vs. 5 µM TBBPA (one-way ANOVA followed by Dunnett's test, p < 0.05) When examining the putative mechanism of TBBPA and OGD synergy we considered calcium imbalance, mitochondrial disfunction and oxidative stress. According to literature data, these processes might be common to both of toxic factors studied here [9,14,22,23,25,27,28,32]. Therefore, using standard methods we measured…”
Section: Ros Mediate Tbbpa and Ogd Synergy In Cgc Culturesmentioning
confidence: 97%
See 4 more Smart Citations
“…# Differences statistically significant vs. 5 µM TBBPA (one-way ANOVA followed by Dunnett's test, p < 0.05) When examining the putative mechanism of TBBPA and OGD synergy we considered calcium imbalance, mitochondrial disfunction and oxidative stress. According to literature data, these processes might be common to both of toxic factors studied here [9,14,22,23,25,27,28,32]. Therefore, using standard methods we measured…”
Section: Ros Mediate Tbbpa and Ogd Synergy In Cgc Culturesmentioning
confidence: 97%
“…The ability of TBBPA to activate the formation of ROS has been observed in vivo in animal models [35,39]. Previous studies by Reistad et al [27,28] demonstrated that TBBPA administered in vitro at low micromolar concentrations significantly increased the fluorescence of DCF in human neutrophil granulocytes and in CGC, which reflects the enhanced production of ROS and the generation of oxidative stress. This finding is corroborated by our present data.…”
mentioning
confidence: 94%
See 3 more Smart Citations